Optimal Placement of Renewable Distributed Generation for Power Losses and Emissions Reduction Using the Multi Verse Optimization Algorithm in Distribution System - Firdaus, Firdaus (TEKNIK, 2025)
Distributed Generation (DG) from renewable energy sources is widely applied in distribution systems or small-scale electric power networks. However, the intermittent and uncertain nature of renewable energy sources requires a mechanism to select and utilize them optimally. The aim of this research is to develop an optimization model for the use of renewable energy sources by determining the placement and size of optimal DG units sourced from renewable energy. Optimal placement and size decisions are obtained by considering emissions or pollution, power losses and voltage profiles in the electric power system. This research uses the Multi Verse Optimization (MVO) method, which is a development of the multiverse theory and the big bang theory. The simulation in this research was carried out on the IEEE 33 bus distribution system.. Simulation results using Matlab software show that the optimal placement and size of distributed generators from renewable energy sources can significantly improve the voltage profile and reduce electrical power losses. The optimal placement and sizing result for 1 DG injection is on bus 6, while when 3 DG injection, the optimal placement is on Bus 13, 24 and 30. This placement location is the same as the research results with other methods or algorithms. Optimizing the installation of three DG renewable energy sources using MVO by considering environmental factors was able to reduce emissions by 71.62 percent. Thus, there is a reduction in costs as environmental compensation of 71.60 percent in the IEEE 33 Bus system.